The conservation and preservation of film and magnetic materials (2): magnetic materials & digital preservation of audio, video and film / Nik Muhammad Hafiz Nik Ibrahim - Nik Ibrahim, Nik Muhammad Hafiz (2015)
Summary of the articles: “The Conservation and Preservation of Film and Magnetic Materials (2): Magnetic Materials” and “Digital Preservation of Audio, Video and Film”